2013
DOI: 10.1007/s00068-013-0263-9
|View full text |Cite
|
Sign up to set email alerts
|

Serum cleaved tau protein and traumatic mild head injury: a preliminary study in the Thai population

Abstract: As it was uncorrelated with traumatic MHI, serum cleaved tau protein proved to be an unreliable biomarker to use in the early detection of and decision-making for traumatic MHI patients at the emergency department.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…1 Wuthisuthimethawee et al reported the mean age in their study as 34.9 AE 15.6 years (range: 15-74), focusing on minor head trauma. 13 In another study by Zemlan et al (1999), mean age was 32.4 AE 14.1 years. 12 These are studies from various geographic regions of the world, and all of them reflect that TBI is more often seen in the most productive age group that comprise a larger part of population and directly have an impact on economy of countries, as they are more involved and exposed to the daily outdoor activities.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…1 Wuthisuthimethawee et al reported the mean age in their study as 34.9 AE 15.6 years (range: 15-74), focusing on minor head trauma. 13 In another study by Zemlan et al (1999), mean age was 32.4 AE 14.1 years. 12 These are studies from various geographic regions of the world, and all of them reflect that TBI is more often seen in the most productive age group that comprise a larger part of population and directly have an impact on economy of countries, as they are more involved and exposed to the daily outdoor activities.…”
Section: Discussionmentioning
confidence: 91%
“…17 No serum cleaved tau protein could be detected by Wuthisuthimethawee et al in 2013 in either the healthy control group or the patients with mild TBI. 13 They concluded that there was no correlation of serum cleaved tau level in mild TBI, thus making it an unreliable marker in early detection and decision making in mild TBI injury patients at the emergency department. Thus, an increase in serum C-tau levels occurring after mild head trauma does not signify it to the tune of diagnostic significance.…”
Section: Discussionmentioning
confidence: 99%
“…4 Several biomarkers have been developed to directly determine the pathology of the nerve cells in the central nervous system (CNS) when it is injured. 5 The blood-brain barrier (BBB), which normally is almost impermeable, can lose its integrity upon brain injury and allow the permeation of molecules into the blood. 6 A number of patients who suffer from mild head injury later on develop significant disabilities.…”
Section: Introductionmentioning
confidence: 99%